Analysis of six CYP450 genetic variants regarding the response to cannabidiol combined with anticonvulsant medication in mexican patients with drug-resistant epilepsy - Feria-Romero, Iris A.; Rocha, Luisa; Reyes-Cuayahuitl, Araceli; Martínez-Juárez, Iris; San-Juan, Daniel; Escamilla-Nuñez, Consuelo; Orozco-Suarez, Sandra (Frontiers in Pharmacology, 2025)
BackgroundCannabidiol (CBD) reduces the frequency of seizures in individuals with specific epileptic syndromes, but its effectiveness for other types of drug-resistant epilepsy (DRE) is unclear. CYP450 enzymes primarily metabolize CBD. The aim of this study was to identify CYP450 genotypes regarding the response of CBD treatment concomitant with anti-seizure drugs in patients with DRE.MethodsThis observational, retrospective, comparative study examined patients with DRE who incorporated CBD into their treatment. Genomic DNA was extracted from the patients’ blood. Patients were divided into two groups: CBD responders and CBD non-responders. Six genetic variants of CYP450 genes were analyzed using real-time polymerase chain reaction (PCR). Statistical significance was determined using Fisher’s exact, chi-squared, and Mann–Whitney U tests. The analysis of polymorphisms involved a statistical test for proportion differences of more than 10% between the comparison groups.ResultsThis study examined 47 patients with DRE, of which 68% showed a positive response to CBD treatment in combination with their current medications. Among the patients who did not respond to adjuvant treatment with CBD, the CYP3A4 *1/rs2242480 genotype was present in 50%. These patients exhibited focal seizures along with various lesions in imaging studies. In contrast, the CYP2B6 *1/*2 and *2/*2 genotypes were identified in 42% of patients with drug-resistant epilepsy who did respond to CBD treatment. These patients had unknown causes of their epilepsy and showed expected results in imaging studies.ConclusionTreatment with CBD reduced seizures in most patients (68%), which was independent of etiology and seizure type. The genotype CYP3A4 *1/rs2242480 may be associated with low response to CBD.